Digital Marketing and Brand Image as Determinants of Customer Trust and Booking Intention: A Study of Hotels in Medan - Lili Suryati; Mila Rachmawati; Andyan Pradipta Utama; Nunung Ayu Sofiati; Andriasan Sudarso (Dinasti Publisher, 2026)
The hotel industry has increasingly adopted digital marketing strategies to remain competitive in the era of online travel platforms and information transparency. In this context, digital marketing activities and brand image are expected to play a critical role in building customer trust and influencing booking intention. This study aims to analyze the effect of digital marketing and brand image on customer trust and booking intention, with customer trust positioned as a mediating variable. The research focuses on three-star hotels in Medan City as the object of analysis. This study employed a quantitative approach using a survey method. The population consisted of hotel guests who stayed at five three-star hotels in Medan City during the period from August to December 2025, with a total population of 4,100 guests. The sample size was determined based on Structural Equation Modeling (SEM) requirements, using five times the number of indicators. With 45 measurement indicators, a total of 225 respondents were selected using proportional sampling from each hotel. Data were analyzed using SEM to test both direct and indirect relationships among variables. The results indicate that digital marketing has a positive and significant effect on customer trust. Brand image is also found to significantly influence customer trust. Furthermore, customer trust has a positive and significant effect on booking intention. The mediation analysis shows that customer trust partially mediates the relationship between digital marketing and booking intention, as well as between brand image and booking intention. These findings suggest that digital marketing and brand image contribute to booking intention primarily through the formation of customer trust. This study contributes to the hospitality and marketing literature by providing empirical evidence from the hotel industry, particularly three-star hotels in Medan City. Practically, the findings imply that hotel managers should prioritize credible digital marketing communication and consistent brand image development to strengthen customer trust and increase booking intention.